Grape by-products from the wine industry – an untapped sustainable resource for application in animal skin health preservation and treatment - Chen, Wanting; Pandey, Preeti; Ziora, Zyta M.; Jayasree, Anjana; Parekh, Harendra S. (Frontiers in Pharmacology, 2025)
The all-wine industry is projected to generate over US$528 billion in sales globally by 2025, and like many mass-producing industries, it too generates significant waste and by-products, much of which ends up in landfill. Among the various agricultural and industrial by-products, residues from winemaking stand out for their exceptionally rich and diverse bioactive compound content, primarily originating from grape skins, seeds and stems, all of which are rich in polyphenols, organic acids and tannins. These compounds have remarkable antioxidant, antimicrobial and anti-inflammatory properties and can therefore be diverted to agricultural, food preservation, cosmetic and pharmaceutical industries. The mechanism of action of the array of bioactive compounds includes disruption of microbial cell membranes, reduction of oxidative stress, and modulation of inflammatory responses. The current literature is limited to highlights of the scale of waste generated, and the application of its bioactive agents, however, it is notably absent of critical appraisal and discussion in sustainable avenues for development and value-added products, which are comprehensively elaborated herein.